Tubulointerstitial nephritis and uveitis – case report - Kwiatkowska, Ewa; Turno-Kręcicka, Anna; Berus, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Tubulointerstitial nephritis and uveitis syndrome is a rare autoimmune disease of incompletely understood pathogenesis. Over 250 cases have been reported in the literature till now, yet the diagnostic process can still be confusing, as the symptoms may occur randomly and vary. Here we report a case of a 52-year-old male with a very atypical clinical manifestation of tubulointerstitial nephritis and uveitis syndrome. Typically, the onset of the syndrome is marked with anterior uveitis concomitant with tubulointerstitial nephritis. In the reported case, though, retinitis persisted for a relatively long time and only after a few years the patient developed symptoms of anterior uveitis.